2002
DOI: 10.1046/j.1460-9568.2002.02000.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective chronic stress‐induced in vivo ERK1/2 hyperphosphorylation in medial prefrontocortical dendrites: implications for stress‐related cortical pathology?

Abstract: Stress has been shown to affect brain structural plasticity, promote long-term changes in multiple neurotransmitter systems and cause neuronal atrophy. However, the mechanisms involved in these stress-related neural alterations are still poorly understood. Mitogen-activated protein kinase (MAPK) cascades play a crucial role in the transduction of neurotrophic signal from the cell surface to the nucleus and are implicated in the modulation of synaptic plasticity and neuronal survival. An intriguing possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 63 publications
6
69
0
1
Order By: Relevance
“…Stress hormones and 5-HT may act in an opposite manner Á stress hormones decrease BDNF levels while 5-HT increases them. The reduction of BDNF could be the result of the decrease in CREB as shown in animal studies (Trentani et al 2002). The loss of BDNF in chronic stress leads to an altered output from areas such as the hippocampus to the pre-frontal cortex.…”
Section: Neurotrophic Factorsmentioning
confidence: 95%
“…Stress hormones and 5-HT may act in an opposite manner Á stress hormones decrease BDNF levels while 5-HT increases them. The reduction of BDNF could be the result of the decrease in CREB as shown in animal studies (Trentani et al 2002). The loss of BDNF in chronic stress leads to an altered output from areas such as the hippocampus to the pre-frontal cortex.…”
Section: Neurotrophic Factorsmentioning
confidence: 95%
“…Although acute stress and the events that follow have evolved as an adaptation, and are therefore beneficial, too great or too long of a response can be detrimental to the body. For example, synaptic plasticity in adult rats was negatively affected by prolonged stress exposure (Trentani et al 2002). In humans, continuous or repeated psychological stress is strongly associated with detrimental effects on the cardiovascular system, and through it, with obesity and hypertension (McEwen 1998;Phillips et al 2012;Sedova et al 2004).…”
Section: Stressmentioning
confidence: 99%
“…8 A number of studies have now provided compelling evidence that neural plasticity and cognitive function can be enhanced by both BDNF and positive AMPA receptor modulation. 9,10 The ampakine, CX1837, has attracted considerable attention, as it is a positive allosteric modulator of AMPA receptors that under homeostatic conditions stimulates and increases BDNF mRNA and protein levels. 11,12 We have recently showed that CX1837 enhances poststroke functional recovery in young animals.…”
Section: Introductionmentioning
confidence: 99%